2021
DOI: 10.3389/fpls.2021.637976
|View full text |Cite
|
Sign up to set email alerts
|

Proteostatic Regulation of MEP and Shikimate Pathways by Redox-Activated Photosynthesis Signaling in Plants Exposed to Small Fungal Volatiles

Abstract: Microorganisms produce volatile compounds (VCs) with molecular masses of less than 300 Da that promote plant growth and photosynthesis. Recently, we have shown that small VCs of less than 45 Da other than CO2 are major determinants of plant responses to fungal volatile emissions. However, the regulatory mechanisms involved in the plants’ responses to small microbial VCs remain unclear. In Arabidopsis thaliana plants exposed to small fungal VCs, growth promotion is accompanied by reduction of the thiol redox of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Although transcript abundance on its own cannot be used to infer changes in the proteome and fluxes in central metabolism ( Nakaminami et al, 2014 ; Schwender et al, 2014 ), this indicated that enhanced incorporation of cytosolic G6P into chloroplasts caused by increased GPT2 expression in leaves could be involved in the plant’s response to small VCs. However, our differential proteomic analyses did not detect any statistically significant accumulation of GPT2 protein in leaves promoted by small VCs ( Supplemental Tables S1 and S2 ; Sánchez-López et al, 2016b ; Ameztoy et al, 2021 ). These analyses also did not detect statistically significant higher levels of GPT2 protein in WT leaves than in gpt2-1 and pgi1-2gpt2-1 leaves ( Supplemental Tables S3, S6, and S7 ).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Although transcript abundance on its own cannot be used to infer changes in the proteome and fluxes in central metabolism ( Nakaminami et al, 2014 ; Schwender et al, 2014 ), this indicated that enhanced incorporation of cytosolic G6P into chloroplasts caused by increased GPT2 expression in leaves could be involved in the plant’s response to small VCs. However, our differential proteomic analyses did not detect any statistically significant accumulation of GPT2 protein in leaves promoted by small VCs ( Supplemental Tables S1 and S2 ; Sánchez-López et al, 2016b ; Ameztoy et al, 2021 ). These analyses also did not detect statistically significant higher levels of GPT2 protein in WT leaves than in gpt2-1 and pgi1-2gpt2-1 leaves ( Supplemental Tables S3, S6, and S7 ).…”
Section: Discussionmentioning
confidence: 67%
“…Predicted locations of these proteins using the SUBA4 Arabidopsis protein subcellular localization database ( Hooper et al, 2017 ) included almost all cellular compartments, but the locations associated with the greatest number of proteins were the cytosol and plastid ( Supplemental Table S1 and Supplemental Figure S3B ). Nearly 70% of these proteins were identified as differentially expressed by small VCs in a previous differential proteomic study using a Col-O background ( Ameztoy et al, 2021 ) ( Supplemental Table S1 ). No statistically significant changes in the levels of GPT2 protein were observed upon small fungal VC treatment ( Supplemental Table S2 ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Recent studies have shown that this capacity also extends to VCs emitted by phytopathogens and microorganisms that do not normally interact mutualistically with plants ( Ezquer et al, 2010 ; Bitas et al, 2015 ; Sánchez-López et al, 2016 ; Cordovez et al, 2017 ; Li et al, 2018 ; García-Gómez et al, 2019 , 2020 ; Moisan et al, 2019 ), although several lines of evidence indicate that the mechanisms involved in some plants’ responses to VCs emitted by beneficial and pathogenic microorganisms are different ( Hernández-Calderón et al, 2018 ; García-Gómez et al, 2020 ). In Arabidopsis , enhanced growth and photosynthesis promoted by air application of fungal VCs is associated with increases in levels of active forms of cytokinins (CKs), photosynthetic pigments and transitory starch in leaves, together with reductions in abscisic acid (ABA) contents, and changes in the transcriptome and proteome through mechanisms involving signaling of redox-activated photosynthesis and long-distance communication between roots and the aerial part of the plant ( Zhang et al, 2008 ; Sánchez-López et al, 2016 ; Ameztoy et al, 2019 , 2021 ; García-Gómez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%